2017
DOI: 10.1002/chem.201700660
|View full text |Cite
|
Sign up to set email alerts
|

d‐Cysteine Ligands Control Metal Geometries within De Novo Designed Three‐Stranded Coiled Coils

Abstract: While metal ion binding to naturally occurring L-amino acid proteins is well documented, understanding the impact of the opposite chirality (D) amino acids on the structure and stereochemistry of metals is in its infancy. We examine the effect of a D-configuration cysteine within a designed L-amino acid three-stranded coiled coil in order to enforce a precise coordination number on a metal center. The D-chirality does not alter the native fold, but the side-chain reorientation modifies the sterics of the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
(275 reference statements)
1
10
0
Order By: Relevance
“…The Hg II ‐S bond distance in the Hg II S Zn(II) N (GRAND‐CSL16CL30H) 3 + crystal structure (PDB code: 5KB1; PDB=Protein Data Bank) has been reported to be 2.38 Å, which is in good agreement with an X‐ray absorption result for Hg II (TRIL16C) 3 − (2.43 Å) . At the same time, the extended X‐ray absorption fine structure (EXAFS) result for the Cd II −S bond length for the trigonal planar Cd II (TRIL16Pen) 3 − is 2.46 Å, which leads one to predict the trigonal planar structures of Hg II S 3 and Cd II S 3 are similar. Thus, regardless of the metal size difference, the crystallographic Hg II S 3 structures could be used to explain general characteristics of Cd II S 3 .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The Hg II ‐S bond distance in the Hg II S Zn(II) N (GRAND‐CSL16CL30H) 3 + crystal structure (PDB code: 5KB1; PDB=Protein Data Bank) has been reported to be 2.38 Å, which is in good agreement with an X‐ray absorption result for Hg II (TRIL16C) 3 − (2.43 Å) . At the same time, the extended X‐ray absorption fine structure (EXAFS) result for the Cd II −S bond length for the trigonal planar Cd II (TRIL16Pen) 3 − is 2.46 Å, which leads one to predict the trigonal planar structures of Hg II S 3 and Cd II S 3 are similar. Thus, regardless of the metal size difference, the crystallographic Hg II S 3 structures could be used to explain general characteristics of Cd II S 3 .…”
Section: Introductionsupporting
confidence: 70%
“…The Hg II -S bond distance in the Hg II S Zn(II) N (GRAND-CSL16CL30H) 3 + crystal structure (PDB code:5 KB1;P DB = Protein Data Bank) has been reported to be 2.38 , [13] which is in good agreement with an X-ray absorption result for Hg II (TRIL16C) 3 À (2.43 ). [7] At the same time, the extended X-ray absorption fine structure (EXAFS) result for the Cd II ÀSb ond length for the trigonal planar Cd II (TRIL16Pen) 3 À is 2.46 , [29] which leads one to predict the trigonal planar structures of Hg II S 3 and Cd II S 3 are similar.T hus, regardless of the metal size difference, the crystallographic Hg II S 3 structures could be used to explain general characteristics of Cd II S 3 .I nt his study,w e have also achieved av ariety of crystal structures based on the sequences designed for Cd II studies. We have obtained the Hg II (GRAND-CSL12AL16C) 3 À ,r epresenting the TRIL12AL16C environment, toa nalyze the effect of Ala (12th position) above the metal site in comparison with the 12 Leu packing of the known Hg II S Zn(II) N (GRAND-CSL16CL30H) 3 + .…”
Section: Introductionmentioning
confidence: 92%
“…These units considerably expand polypeptide templates that possibly pave ways toward designing novel peptide architectures. Until our work, no studies have been reported that use d -amino acids to engineer metal environments or to control metal geometries [4, 5, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing the coordination number of Cd II bound in TRI systems revealed that while a mixture of CdS 3 and CdS 3 O species were formed in Cd(TRIL16C) 3 − , only CdS 3 O was obtained in Cd( TRI L12AL16C) 3 − or Cd( TR L16 D C) 3 −. [17, 18] Furthermore, the introduction of greater steric encumbrance in the Cd( TRI L12 D LL16C) 3 − construct resulted in exclusive CdS 3 while providing greater proximal space to the metal binding site in Cd(GRCSL16CL19 D L) 3 − led to the formation of CdS 3 O 2 . [19] These studies demonstrated that modification of steric bulk around the metal-binding site could control solvent/substrate access to the metal.…”
mentioning
confidence: 99%